Designing Supplementary Materials Entitled “Learning Recount Texts through Local Photograph” For Reading Recount Text - Eka Novi Dianti; Yanti Sri Rezeki; Eni Rosnija (Universitas Muhammadiyah Kalimantan Timur, 2023)
The purpose of this study was to create supplementary material to assist teachers in teaching recount text to tenth-grade students. This study used development research with the ADDIE instructional model. Due to time constraints, only three stages were carried out: analysis, design, and development. According to the findings of the needs analysis phase, teachers had difficulty finding appropriate supplementary material about recount text. The design phase focused on how the researcher designed the product's draft by focusing on six factors: learning objectives, topic, language skill, text genre, grammar, and task. During the development phase, the researcher used Microsoft Word and Adobe Photoshop software to develop materials. Microsoft Word was used to create the content, and Adobe Photoshop was used to create the illustration. Internal validation was also performed in this study to determine whether or not the supplementary materials met the standard. The researcher received a percentage score of 95.8 percent for the content of supplementary material (very good criteria), while the illustration received a score of 100 percent (very good criteria). This implied that the materials were appropriate and capable of supporting recount text teaching and learning.